The pursuit of liberty : how Hamilton vs. Jefferson ignited the lasting battle over power in America - Rosen, Jeffrey, 1964- (Simon & Schuster, 2025)
In The Pursuit of Liberty, Jeffrey Rosen explores the clashing visions of Hamilton and Jefferson about how to balance liberty and power in a debate that continues to define -- and divide -- our country: Jefferson championed states' rights and individual liberties, while Hamilton pushed for a strong Federal government and a powerful executive. This ongoing tug-of-war has shaped all the pivotal moments in American history, including Abraham Lincoln's fight against slavery and southern secession, the expansion of federal power under Franklin Roosevelt's New Deal, and Ronald Reagan's and Donald Trump's conservative push to shrink the size of the federal government. Rosen also shows how Hamilton and Jefferson's disagreement over how to read the Constitution has shaped landmark debates in Congress and the Supreme Court about executive power, from John Marshall's early battles with Andrew Jackson to the current divisions among the justices on issues from presidential immunity to control over the administrative state. More than ever, the clash between Hamiltonian and Jeffersonian ideals resonates today in our most urgent national debates over the question of whether modern presidents are consolidating power and subverting the Constitution -- the very threat to American democracy that both Hamilton and Jefferson were determined to avoid. The Pursuit of Liberty is a compelling history of the opposing forces that have shaped our country since its founding, and the ongoing struggle to define the balance between liberty and power. --